Let n be 14*2*2. Let w = -19 + 33. Let y be (-1 + w/10)*10. Solve y*r = 3*r + n for r.

1

Let r be (226)/((-3)/(-9)). Solve -4*g - r = 1 for g.

-3

Let k = 4 + 5. Let d = 14 - k. Solve -d*w + 0*w = 25 for w.

-5

Let x = 18 + -12. Suppose 2*g - x = -g. Solve s = -g*s for s.

0

Let f(y) = -y**2 + 4*y - 1. Let l be f(2). Suppose -3*w = l*q - q + 4, -2 = -4*q - w. Let s be 3 - (q - 1) - -17. Solve z + 4*z - s = 0 for z.

4

Let a be (-1)/(2*2/(-20)). Let c be 2/(-2) - 3/(-3). Suppose c*q - a = -q. Solve 6 = -q*m - 19 for m.

-5

Let n(b) = b3 - 8*b2 - 8*b - 5. Let o be n(9). Solve 0 = 3*a - o*a for a.

0

Let j© = -c**2 + 5*c - 4. Let y be j(4). Suppose -5*i = -y*i. Let m be (1 - 1)/(-1) + 6. Solve i = 2*f + 2 + m for f.

-4

Let j(s) be the second derivative of -s**32 + 6*s. Let v be j(-2). Solve u - v*u = 0 for u.

0

Let d be -2 + (0 + -3 - 2). Let f = 9 + d. Solve 0 = -y - f*y for y.

0